THE ROLE OF DATE-INFUSED WATER IN INDONESIAN PREGNANCY: EXAMINING ITS NUTRITIONAL VALUE AND IMMUNOMODULATORY EFFECTS - Amaliah , Fatimah Suryono; Agus , Priyanto Widodo; Puspita, Dewi Lestari; Muhammad , Adib Santoso (Global Journal of Medical and Health Science, 2023)
Pregnancy is a critical phase in a woman’s life, demanding adequate nutrition and immune system support. In Indonesia, maternal health is of paramount importance, and exploring natural remedies such as date-infused water offers a unique perspective. This study investigates the nutritional value and immunomodulatory effects of date-infused water in Indonesian pregnancy. The research employed a mixed-methods approach, combining surveys and laboratory analyses. Pregnant women from various regions of Indonesia participated, providing insights into their dietary habits and the incorporation of date-infused water into their daily routines. The nutritional composition of date-infused water was assessed, focusing on essential micronutrients. The findings revealed that date-infused water is a popular traditional remedy among Indonesian pregnant women. It is appreciated not only for its refreshing taste but also for its potential health benefits. The analysis of date-infused water confirmed its richness in key nutrients, including vitamins, minerals, and dietary fiber. Vitamin C, in particular, was found in significant quantities, which can contribute to the enhancement of maternal immunity. Moreover, the study demonstrated that regular consumption of date-infused water had positive immunomodulatory effects, contributing to improved maternal health during pregnancy. The combination of natural antioxidants and micronutrients in date-infused water supported the immune system’s function, potentially reducing the risk of infections and complications. In conclusion, date-infused water plays a valuable role in Indonesian pregnancy by providing essential nutrients and immunomodulatory benefits. Its inclusion in the maternal diet can be considered a practical and culturally relevant approach to supporting maternal and fetal health. Further research and public health initiatives can harness the potential of date-infused water to enhance pregnancy outcomes in Indonesia.